2012
DOI: 10.1016/j.cbpa.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diterpene synthases: new opportunities for mechanistic enzymology and engineered biosynthesis

Abstract: Diterpenoid biosynthesis has been extensively studied in plants and fungi, yet cloning and engineering diterpenoid pathways in these organisms remain challenging. Bacteria are emerging as prolific producers of diterpenoid natural products, and bacterial diterpene synthases are poised to make significant contributions to our understanding of terpenoid biosynthesis. Here we will first survey diterpenoid natural products of bacterial origin and briefly review their biosynthesis with emphasis on diterpene synthase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 68 publications
3
86
0
Order By: Relevance
“…It is believed that these three domain (γβα) proteins found in fungi and plants are the result of an ancient fusion event of bacterial class I (α) and class II (γβ) terpenoid synthases. In fact, typical bacterial diterpene synthases are not fused, and cyclization involves class II (γβ) and class I (α) terpenoid synthases for this twostep cyclization mechanism [181]. In plants, however, many three-domain (γβα) diterpene synthases are monofunctional and catalyze either a protonation-or an ionization-dependent cyclization reaction (on a bicyclic diphosphate or GGPP) because the other domain is not functional [180].…”
Section: Schmidt-dannertmentioning
confidence: 99%
“…It is believed that these three domain (γβα) proteins found in fungi and plants are the result of an ancient fusion event of bacterial class I (α) and class II (γβ) terpenoid synthases. In fact, typical bacterial diterpene synthases are not fused, and cyclization involves class II (γβ) and class I (α) terpenoid synthases for this twostep cyclization mechanism [181]. In plants, however, many three-domain (γβα) diterpene synthases are monofunctional and catalyze either a protonation-or an ionization-dependent cyclization reaction (on a bicyclic diphosphate or GGPP) because the other domain is not functional [180].…”
Section: Schmidt-dannertmentioning
confidence: 99%
“…34) These results suggest not only that two distinct pathways (Fig. 4, pathways A and B), which use E,E-FPP and E,E,E-GGPP respectively as substrates of Mvan 3822, are utilized to biosynthesize sesquarterpenes (13)(14)(15)(16)(17)(18) in the cells, and also that polyprenyl reductase (PR) can reduce both the Z and the E double bonds at C-14 of compounds 20 and 21. 34) In 2012, a new sesquarterpene, 18, was isolated from M. chlorophenolicum cells grown to stationary phase.…”
Section: Unique Biosynthesis Of Sesquarterpenes (C 35 Terpenes) Imentioning
confidence: 97%
“…31) It has been reported that many terpene cyclases have broad substrate specificities, and that other classes of terpenes have been created in vitro. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] A combination of studies identifying enzymatic products biosynthesized from unusual substrates and the analysis of genome sequences should lead not only to the discovery of additional functions of these enzymes in the organism, but also to the identification of novel natural terpenoids that have functions in their producers.…”
Section: Identification Of Bifunctional Sesquarterpene/ Triterpene Cymentioning
confidence: 99%
See 2 more Smart Citations